1968
DOI: 10.1071/ar9680721
|View full text |Cite
|
Sign up to set email alerts
|

Survival and seasonal germination of seeds of Avena fatua and A. ludoviciana

Abstract: The effects of soil type, temperature, and moisture on the survival and seasonal germination of seeds of A. fatua and A. ludoviciana, buried at five depths in the soil, were studied in a glasshouse experiment. Seeds of both species germinated only when mean weekly minimum temperatures were below 20°C and mean weekly maxima below 28°. A. fatua germinated better than A. ludoviciana in the 20–30° range and was therefore the dominant species in autumn germinations of wild oats. Both species germinated throughout w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
7
22
0
Order By: Relevance
“…At the same time, seeds placed in the clay soil lost their dormancy faster than those placed in the sandy loam soil and thus had a lower number of viable and germinable seeds. Greater germination of Melaleuca quinquenervia was found in clay soils (Van et al 2005) but these results are in contrast to those of Benvenuti (2003) and Quail and Carter (1968) who found that soil with a pronounced clay matrix impeded the germination of buried seeds and induced seed dormancy in certain weed species.…”
Section: Soilmentioning
confidence: 48%
“…At the same time, seeds placed in the clay soil lost their dormancy faster than those placed in the sandy loam soil and thus had a lower number of viable and germinable seeds. Greater germination of Melaleuca quinquenervia was found in clay soils (Van et al 2005) but these results are in contrast to those of Benvenuti (2003) and Quail and Carter (1968) who found that soil with a pronounced clay matrix impeded the germination of buried seeds and induced seed dormancy in certain weed species.…”
Section: Soilmentioning
confidence: 48%
“…Non-indigenous Mediterranean weeds are also shown to prefer cooler conditions for germination; for example, the seeds of Lolium and Avena did not germinate well above 26 and 20°C respectively (Quail and Carter 1968;Gramshaw 1976). The germination rate for the first collected samples was therefore greatest between March and June, ceasing in July (Figure 3), a period that also marks the end of winter season.…”
Section: Seedling Densities and Plant Species Emerging From Dungmentioning
confidence: 94%
“…The demographic behaviour of this species (hereafter referred to as A. ludoviciana appears to be considerably different from that of A. fatua. Other studies have shown the contrasting behaviour of these two species in their dormancy patterns and their temperature requirements for germination (Quail & Carter 1968, 1969, two characteristics that may have a marked influence on the demography of their populations. Similar differences were found in studies carried out in Australia (Quail & Carter 1968).…”
Section: Introductionmentioning
confidence: 99%
“…ludoviciana (Durieu) Nyman) is the most widely distributed and abundant Avena species in Spain (Garcia, Baudin & Salto 1978) and in other regions of Mediterranean climate (Quail & Carter 1968;Thurston & Phillipson 1976). ludoviciana (Durieu) Nyman) is the most widely distributed and abundant Avena species in Spain (Garcia, Baudin & Salto 1978) and in other regions of Mediterranean climate (Quail & Carter 1968;Thurston & Phillipson 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation